THE LANGUAGE OF PICTURES: THE ROLE OF TROPES IN THE FORMATION OF POETIC THINKING (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article examines the significance of tropes as key elements that form poetic thinking and language picture of the world. The author analyses the functions of tropes in a fiction text, their role in creating imagery and expressiveness of speech, as well as the peculiarities of their use in Russian, Uzbek and English languages. Special attention is paid to cultural and linguistic differences in the understanding and translation of tropes, which is demonstrated by examples of literary works.